Characterization of sediment contamination and benthic habitat response in mangrove ecosystems of Hainan Province - Zheng, Fa; Huang, Zanhui; Chen, Zeheng; Liu, Jiahui; Zhou, Mingliang; Ding, Weipin; Guo, Xiong; Chen, Liang; Wang, Zhaofan; Xu, Yan (Frontiers in Marine Science, 2025)
IntroductionChina's rapid economic growth has led to escalating environmental pollution, significantly impacting mangrove ecosystems. The persistence and response to pollution in mangrove ecosystems involve multiple processes, including the accumulation of contaminants in sediments, their transport in plants, and their accumulation in other organisms. However, comprehensive studies on the multidimensional interactions among these processes are limited. MethodsThis study investigated two mangrove forest areas in Hainan, which were categorized according to the type of mangrove forest cover: planted forests and natural forests. Thirty sampling sites were established to collect data on benthic organisms and their sediment characteristics. ResultsElemental As showed moderate, ongoing pollution. The distribution of species in the two regions showed significant population differences. The benthic population density in the natural forest was significantly lower than that in the planted forest, which was mainly due to the prevalence of Batillaria cumingi, and biodiversity indices and habitats in the natural forest were superior to those in the planted forest, which mainly depended on the degree of anthropogenic disturbance. Total phosphorus, nitrogen, dissolved solids, Hg, and sand grains were the most important variables. DiscussionTotal phosphorus and total nitrogen were the most important environmental factors affecting community composition, while total dissolved solids influenced overall changes in species composition, highlighting the significant influence of the type of mangrove cover on sediment pollution and environmental factors, leading to significant changes in the biomass and density of benthic organisms. This study emphasizes the complex interactions among sediment contamination, mangrove cover, and benthic communities, providing a three-dimensional view of the distribution patterns of mangrove contamination.